Krisis Kebudayaan Islam dan Gagasan Ismail Raji Al-Faruqi - Farkhan Fuady (Literasi : Jurnal Kajian Keislaman Multi-Perspektif, 2022)
Culture in the community environment develops and is preserved by the community. More and more these cultures interact with other cultures. These interactions lead to a cultural crisis, in which social changes occur that lead to a decline. Ismail Raji al-Faruqi is one of the leading Muslim scholars who initiated Islamic culture. This article aims to describe the idea of Ismail Raji al-Faruqi's Islamic culture. The idea is expected to be able to answer the phenomenon of the cultural crisis. By using descriptive analysis, this article shows that al-Faruqi's idea of Islamic culture basically focuses on seeing people's awareness of Islamic values. Muslims are expected to realize that they are creatures of God.